Recent Developments in the Metal-Catalyzed Synthesis of Nitrogenous Heterocyclic Compounds - Xueguo Zhang; Wenxuan Bi; Zhenyu Cao; Jian Shen; Baohua Chen (Molecules)
Metal-catalyzed cyclization reactions have become a powerful and efficient approach for the stereoselective construction of both carbocyclic and heterocyclic ring systems. Transition metal complexes, with their ability to activate and selectively functionalize organic substrates, have revolutionized various areas of synthetic chemistry. This review highlights recent advancements in metal-catalyzed cyclization reactions, especially in the synthesis of nitrogen-containing heterocycles like imidazoles, pyridines, pyrimidines, and indoles. These advancements have significantly impacted fields such as natural product synthesis, pharmaceuticals, functional materials, and organic electronics. Novel catalytic systems, ligand designs, and reaction conditions continue to expand the capabilities of these reactions, driving further the progress made in synthetic organic chemistry. This review provides a comprehensive overview of recent research.